Welcome to Westonci.ca, where your questions are met with accurate answers from a community of experts and enthusiasts. Get quick and reliable solutions to your questions from a community of experienced experts on our platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
Sure, let's solve the equation [tex]\( 4w^2 = 15w + 4 \)[/tex].
First, we set the equation to zero by bringing all terms to one side:
[tex]\[ 4w^2 - 15w - 4 = 0 \][/tex]
This is a quadratic equation in the standard form [tex]\( ax^2 + bx + c = 0 \)[/tex].
Here, [tex]\( a = 4 \)[/tex], [tex]\( b = -15 \)[/tex], and [tex]\( c = -4 \)[/tex].
To solve the quadratic equation, we use the quadratic formula:
[tex]\[ w = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
Substitute [tex]\( a = 4 \)[/tex], [tex]\( b = -15 \)[/tex], and [tex]\( c = -4 \)[/tex] into the formula:
[tex]\[ w = \frac{-(-15) \pm \sqrt{(-15)^2 - 4 \cdot 4 \cdot (-4)}}{2 \cdot 4} \][/tex]
[tex]\[ w = \frac{15 \pm \sqrt{225 + 64}}{8} \][/tex]
[tex]\[ w = \frac{15 \pm \sqrt{289}}{8} \][/tex]
[tex]\[ w = \frac{15 \pm 17}{8} \][/tex]
Now, we solve for the two possible values of [tex]\( w \)[/tex]:
For the positive case:
[tex]\[ w = \frac{15 + 17}{8} \][/tex]
[tex]\[ w = \frac{32}{8} \][/tex]
[tex]\[ w = 4 \][/tex]
For the negative case:
[tex]\[ w = \frac{15 - 17}{8} \][/tex]
[tex]\[ w = \frac{-2}{8} \][/tex]
[tex]\[ w = -\frac{1}{4} \][/tex]
So, the solutions to the equation [tex]\( 4w^2 = 15w + 4 \)[/tex] are:
[tex]\[ w = 4, -\frac{1}{4} \][/tex]
First, we set the equation to zero by bringing all terms to one side:
[tex]\[ 4w^2 - 15w - 4 = 0 \][/tex]
This is a quadratic equation in the standard form [tex]\( ax^2 + bx + c = 0 \)[/tex].
Here, [tex]\( a = 4 \)[/tex], [tex]\( b = -15 \)[/tex], and [tex]\( c = -4 \)[/tex].
To solve the quadratic equation, we use the quadratic formula:
[tex]\[ w = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
Substitute [tex]\( a = 4 \)[/tex], [tex]\( b = -15 \)[/tex], and [tex]\( c = -4 \)[/tex] into the formula:
[tex]\[ w = \frac{-(-15) \pm \sqrt{(-15)^2 - 4 \cdot 4 \cdot (-4)}}{2 \cdot 4} \][/tex]
[tex]\[ w = \frac{15 \pm \sqrt{225 + 64}}{8} \][/tex]
[tex]\[ w = \frac{15 \pm \sqrt{289}}{8} \][/tex]
[tex]\[ w = \frac{15 \pm 17}{8} \][/tex]
Now, we solve for the two possible values of [tex]\( w \)[/tex]:
For the positive case:
[tex]\[ w = \frac{15 + 17}{8} \][/tex]
[tex]\[ w = \frac{32}{8} \][/tex]
[tex]\[ w = 4 \][/tex]
For the negative case:
[tex]\[ w = \frac{15 - 17}{8} \][/tex]
[tex]\[ w = \frac{-2}{8} \][/tex]
[tex]\[ w = -\frac{1}{4} \][/tex]
So, the solutions to the equation [tex]\( 4w^2 = 15w + 4 \)[/tex] are:
[tex]\[ w = 4, -\frac{1}{4} \][/tex]
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.